Serum-Free Medium Enhances the Therapeutic Effects of Umbilical Cord Mesenchymal Stromal Cells on a Murine Model for Acute Colitis - Wu, Xiaoyun; Wu, Daocheng; Mu, Yongxu; Zhao, Yuxia; Ma, Zhijie (Frontiers in Bioengineering and Biotechnology, 2020)
The usage of animal serum may ultimately prevent the application of ex vivo cultured mesenchymal stromal cells (MSCs) in a clinical setting due to safety concerns and batch-to-batch variability. Increasing regulatory pressure to limit use of animal serum has been issued and serum-free, xeno-free, and chemically defined media (S&XFM-CD) is encouraged to replace serum-containing media (SCM) in the stem cell preparation process. We previously developed a S&XFM-CD for the expansion of umbilical cord-derived MSCs (UCMSCs). Different culture conditions affect the function of MSCs, which may further affect the therapeutic efficiency and mechanisms of action. In this study, we compared the therapeutic effect and mechanism of UCMSCs in S&XFM-CD (UCMSCS&XFM-CD) in experimental colitis with those in SCM (UCMSCSCM). UCMSCS&XFM-CD exhibited better therapeutic effects than UCMSCSCM by body weight, disease activity index, and histological colitis score. UCMSCS&XFM-CD or UCMSCSCM migrated to the inflammation site of injured colon, but exhibited low levels of recruitment and persistence. Systemic depletion of endogenous macrophages impaired the therapeutic effects of UCMSCSCM and UCMSCS&XFM-CD. Furthermore, UCMSCS&XFM-CD more markedly promoted intestinal macrophage polarisation from M1 to M2 phenotype to produce higher levels of IL-10 and lower levels of TNF-α in colon tissue than UCMSCSCM, while a higher level of IL-4 was produced in UCMSCSCM-treated group. UCMSCS&XFM-CD cocultured with RAW264.7 cells in a transwell system promoted the release of TSG-6 and IL-6, whereas UCMSCSCM increased PGE2 levels. Taken together, we demonstrated that UCMSCs in S&XFM-CD exhibited improved therapeutic effects with altered cytokine secretion in an experimental acute colitis model.